Eco-physiological study on the mangrove forests along Egyptian - African red sea coast - Abdelwahab Afefe Abdelwahab Afefe; Abdelhamid A. Khedr; Amira Shawky Soliman; Mohamed Said Abbas (Cairo : Abdelwahab Afefe Abdelwahab Afefe, 2020)
Due to the importance of mangrove forest to the ecological system, environment, climate change adaptation, mitigation and ecosystem services, it is necessary to understanding the mangrove forests status in Egypt (ecology and physiology), therefore, the aim of the present study was to obtain the basic information needed to evaluate ecology and carbon stock of mangrove forests along Egyptian-African Red Sea coast. The results reached that: In the present study, Avicennia marina trees growing in association with Rhizophora mucronata were taller (mean = 439.6 cm) than plants growing in pure community (mean = 298.6 cm). R. mucronata trees growing in association with A. marina were taller (mean = 431.3 cm) than plants growing in pure community (mean = 250.3 cm). Mangroves showed variations in proline content. The maximal value (23.56 mg/ g dry wt) was recorded in R. mucronata stands in Marsa Sha'ab area, while the minimum value (17 mg/ g dry wt) was recorded in A. marina stands in Marsa Sha'ab area, and there were highly significant differences among species mangroves from different locations and stands. Contents of chlorophyll A in different analyzed mangrove ranged between 4.46 and 6.05 mg./g.F.wt for A. marina, and between 3.69 and 4.29 mg./g.F.wt for R. mucronata. Chlorophyll B content ranged between 1.46 and 1.83 mg./g.F.wt. For A. marina, and between 1.27 and 1.65 mg./g.F.wt. for R. mucronata. Results showed that the carotenoids contents showed a varied greatly in Avicennia marina leaves and the ranged recorded was between 2.94 mg./g.F.wt and 2.29 mg./g.F.wt. And a hight content of carotenoids in R. mucronata recorded 2.09 mg./g.F.wt. Additionally, the mangroves showed variations between the mangrove species in mineral composition at different study locations. In all the locations Na+ and Cl+ ions were dominant than K+, Ca++ and Mg++ ions. For A. marina, a higher value for Na+ (8.22%) and Cl- (7.9%), and the K+ a higher value recorded (1.4 %) and recorded 0.81% and 0.33% for Ca++ and Mg++ respectively
Thesis (Ph.D.) - Cairo University - Faculty of African Postgraduate Studies - Department of Natural Resources
Issued also as CD
Keywords: Carbon Storage; Egypt; Mangrove